2022
DOI: 10.1159/000526897
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of <i>Arsenicum album 30C</i> in the Prevention of COVID-19 in Individuals Residing in Containment Areas: A Prospective, Multicenter, Cluster-Randomized, Parallel-Arm, Community-Based, Open-Label Study

Abstract: Objective During the early part of the COVID-19 pandemic, non-pharmacologic interventions were the strategies for the prevention of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The Ministry of Ayush, Govt. of India, had advised Arsenicum album 30C, as a prophylactic to prevent COVID-19. This study was undertaken to evaluate the protective efficacy and safety of the Arsenicum album 30C. Methods We conducted a prospective, multicentre, cluster-randomized, parallel arm, community-based, open-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Similar observations were also made in previous COVID-19 prophylaxis studies of homeopathic medicine. 27,33 Awareness of the government advisory about AYUSH prophylactics for COVID-19 in more than 60% of the study participants and intake of medicine by 91% of this population reflect on the effectiveness of this governmental strategy in striving to mitigate the pandemic during its first wave.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar observations were also made in previous COVID-19 prophylaxis studies of homeopathic medicine. 27,33 Awareness of the government advisory about AYUSH prophylactics for COVID-19 in more than 60% of the study participants and intake of medicine by 91% of this population reflect on the effectiveness of this governmental strategy in striving to mitigate the pandemic during its first wave.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were also made in previous COVID-19 prophylaxis studies of homeopathic medicine. 27 33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found promising results, with only 0.74% of workers who received the intervention showing symptoms of COVID-19, compared to 67.87% of other workers and 13.35% of teleworkers who did not receive the intervention. Similarly, a cohort study 18 and a prospective, multicenter, community-based, open-label study involving 32186 individuals in 7 Indian cities 19 both showed that the administration of /textitArsenicum album 30C could reduce the occurrence of COVID-19 and offered some protection compared to no treatment. These findings suggest that further research is needed to explore the potential benefits of Arsenicum album 30cH in the prevention and treatment of COVID-19.…”
mentioning
confidence: 98%
“…Despite some methodological limitations, the results are remarkable: only 0.7% of employees taking the drug showed symptoms of COVID-19, compared with 67.8% of workers at other premises and 13.3% of teleworkers who did not receive the intervention. Furthermore, a cohort study 34 as well as a prospective, multicenter, community-based, open-label study of 32,186 people in seven Indian cities, 35 showed that Arsenicum album 30C had some protective effects against COVID-19 compared with no treatment.…”
mentioning
confidence: 99%